“Unreal world” or “real world” data in oral anticoagulant treatment of atrial fibrillation - Freedman, Ben; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2016)
Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.